KONSEP AIR HUJAN DALAM AL-QUR'AN DAN SAINS - Fiya, Nurfiyana Syahrani (Universitas Nahdlatul Ulama Surakarta, 2025)
Water is one of the resources that is very important for life because it has a vital function for the survival of life on this earth, especially rainwater which is said to be a blessing from Allah SWT. This research aims to explore and understand more deeply the concept of rainwater in the Qur'an, especially the process of rainwater and the descent of rain from al-munz. This researchwas prepared using a literature study approach that focuses on data collection techniques, recording and processing research materials. This research uses a qualitative approach based on existing theories and materials. Data collection is done by taking theories from books and journals. The results of this study found that the Qur'an describes rain as a sign of the greatness of Allah SWT and a source of life with its divinely regulated process. Rain not only plays an important role for agriculture and life but as a reminder to humans of the power and grace of Allah SWT. This research is expected to add deeper insight that the truth of the Qur'an can be proven through natural phenomena and various sciences.